REVIEWS: CDS. (Strad, 2000)
Reviews several music recordings. `Stravinsky Concertino,' by Goldner Quartet; `String Quintets op.20 in E minor and op.25 in E major,' by Franz Xaver Gebel; `Chamber Music vol.3 Piano Trios nos. 1 & 2,' by Arthur Foote.